Rāmūz al-aḥādīth ʻalá tartīb ḥurūf al-hijā : sabʻat aqsām - Kumushkhānawī, Aḥmad ibn Muṣṭafá, 1812 or 1813-1893 or 1894, (Early Arabic Printed Books from the British Library.)
[A dictionary of traditions, with a prefatory treatise on the science of tradition, and various readings and glosses on the margin.]